4+[12/15:9/2].15/16
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
4.[-2(8:4) + 15(-3) - (-12)]
= 4.[-2.2 - 45 + 12]
= 4.[-4 - 45 + 12]
= 4.[-49 + 12]
= 4.[-37]
= - 148
3.(25 : 5 - 14 : 2) - 5.(6:2)
= 3.(5 - 7) - 5.3
= 3.(-2) - 15
= - 6 - 15
= -21
a: =-1+17/20=-3/20
b: =(28/60-33/60)*(-25/3)
=(-1/12)*(-25/3)=1/12*25/3=25/36
c: \(=\dfrac{1}{3}\cdot\dfrac{1}{3}=\dfrac{1}{9}\)
a. (7/15 + 8/15) + (22/12 + 2/12)
= 1 + 24/12
= 1 + 2
=3
b.(9/7 + 5/7) + (16/20 + 4/20)
= 14/7 + 20/20
= 2 + 1
= 3
\(a,\dfrac{7}{15}+\dfrac{22}{12}+\dfrac{8}{15}+\dfrac{2}{12}\\ =\left(\dfrac{7}{15}+\dfrac{8}{15}\right)+\left(\dfrac{22}{12}+\dfrac{2}{12}\right)\\ =\dfrac{15}{15}+\dfrac{24}{12}\\ =1+2\\ =3\\ b,\dfrac{9}{7}+\dfrac{16}{20}+\dfrac{4}{20}+\dfrac{5}{7}\\ =\left(\dfrac{9}{7}+\dfrac{5}{7}\right)+\left(\dfrac{16}{20}+\dfrac{4}{20}\right)\\ =\dfrac{14}{7}+\dfrac{20}{20}\\ =2+1\\ =3\)
\(\dfrac{3}{9}+\dfrac{9}{15}+\dfrac{16}{24}=\dfrac{1}{3}+\dfrac{9}{15}+\dfrac{2}{3}=\dfrac{5}{15}+\dfrac{9}{15}+\dfrac{10}{15}=\dfrac{24}{15}=\dfrac{8}{5}\)
\(\dfrac{4}{10}+\dfrac{12}{32}+\dfrac{9}{15}=\dfrac{2}{5}+\dfrac{3}{8}+\dfrac{3}{5}=\dfrac{2}{5}+\dfrac{3}{5}+\dfrac{3}{8}=\dfrac{5}{5}+\dfrac{3}{8}=1+\dfrac{3}{8}=1\dfrac{3}{8}=\dfrac{11}{8}\)
\(\dfrac{1}{6}+\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{18}=\dfrac{3}{18}+\dfrac{9}{18}+\dfrac{6}{18}+\dfrac{1}{18}=\dfrac{19}{18}\)
câu a :
\(\dfrac{-8}{24}+\dfrac{-4}{12}=\dfrac{-1}{3}+\dfrac{-1}{3}=\dfrac{-2}{3}\)
câu b :
\(\dfrac{-20}{35}+\dfrac{16}{24}=\dfrac{-4}{7}+\dfrac{2}{3}=\dfrac{2}{21}\)
câu c :
\(\dfrac{-3}{9}+\dfrac{-6}{15}=\dfrac{-1}{3}+\dfrac{-2}{5}=\dfrac{-11}{15}\)
câu d :
\(\dfrac{3}{13}-\dfrac{4}{10}=\dfrac{3}{13}-\dfrac{2}{5}=\dfrac{-11}{65}\)
câu e :
\(\dfrac{5}{17}-\dfrac{9}{15}=\dfrac{5}{17}-\dfrac{3}{5}=\dfrac{-26}{85}\)
câu g :
\(\dfrac{9}{18}-\dfrac{6}{15}+\dfrac{3}{-9}=\dfrac{9}{18}-\dfrac{6}{15}+\dfrac{-3}{9}\\ =\dfrac{1}{2}-\dfrac{2}{5}+\dfrac{-1}{3}=\dfrac{-7}{30}\)
câu h :
\(\dfrac{5}{4}-\dfrac{1}{2}+\dfrac{-7}{8}=\dfrac{10}{8}-\dfrac{4}{8}+\dfrac{-7}{8}=\dfrac{-1}{8}\)
a; \(\dfrac{3}{11}\) + \(\dfrac{5}{-9}\) + \(\dfrac{4}{11}\) - \(\dfrac{4}{9}\) + \(\dfrac{3}{17}\) + \(\dfrac{15}{11}\)
= (\(\dfrac{3}{11}\) + \(\dfrac{4}{11}\) + \(\dfrac{15}{11}\)) - (\(\dfrac{5}{9}\) + \(\dfrac{4}{9}\)) + \(\dfrac{3}{17}\)
= 2 - 1 + \(\dfrac{3}{17}\)
= 1 + \(\dfrac{3}{17}\)
= \(\dfrac{20}{17}\)
c; N = \(\dfrac{\dfrac{5}{7}-\dfrac{5}{9}-\dfrac{5}{11}}{\dfrac{15}{7}+\dfrac{15}{9}+\dfrac{15}{11}}\)
Phải là - \(\dfrac{5}{7}\) chỗ tử số mới đúng em nhé!
4 + [12/15 : 9/2].15/16 = 25/6
tk mk nha !!!!~~
Dung roi